2016
DOI: 10.1186/s12885-016-2337-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced immunity in a mouse model of malignant glioma is mediated by a therapeutic ketogenic diet

Abstract: BackgroundGlioblastoma multiforme is a highly aggressive brain tumor with a poor prognosis, and advances in treatment have led to only marginal increases in overall survival. We and others have shown previously that the therapeutic ketogenic diet (KD) prolongs survival in mouse models of glioma, explained by both direct tumor growth inhibition and suppression of pro-inflammatory microenvironment conditions. The aim of this study is to assess the effects of the KD on the glioma reactive immune response.MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(95 citation statements)
references
References 50 publications
0
94
0
1
Order By: Relevance
“…Finally, ketones and the KD have been shown to affect the immune system (Kim D. Y. et al, 2012; Husain et al, 2013; Rahman et al, 2014; Youm et al, 2015), and we have shown that the KD also reverses tumor-mediated immune suppression in a mouse model of malignant glioma (Lussier et al, 2016). As radiation-induced tumor killing is known to expose the immune system to a greater diversity of tumor antigens, it is possible that the KD as an adjuvant works to augment the effect of radiation in part by enhancing immunity against GBM.…”
Section: Kd In Combination With Standard Therapiesmentioning
confidence: 67%
See 1 more Smart Citation
“…Finally, ketones and the KD have been shown to affect the immune system (Kim D. Y. et al, 2012; Husain et al, 2013; Rahman et al, 2014; Youm et al, 2015), and we have shown that the KD also reverses tumor-mediated immune suppression in a mouse model of malignant glioma (Lussier et al, 2016). As radiation-induced tumor killing is known to expose the immune system to a greater diversity of tumor antigens, it is possible that the KD as an adjuvant works to augment the effect of radiation in part by enhancing immunity against GBM.…”
Section: Kd In Combination With Standard Therapiesmentioning
confidence: 67%
“…D’Agostino and co-workers have added hyperbaric oxygen and ketone supplementation to demonstrate reduced tumor cell growth and metastatic spread in the VM metastatic tumor model (Poff et al, 2014, 2015). We used the syngeneic intracranial GL261-luc/albino C57/Bl6 model to demonstrate that CR was not necessary for the anti-tumor effects of the KD (Stafford et al, 2010), particularly when a 4:1 fat:carbohydrate plus protein formulation is used (Scheck et al, 2012; Woolf et al, 2015; Lussier et al, 2016). Recently Martuscello et al (2016) demonstrated inhibition of glioma stem cell growth in vitro and in vivo through the use of a supplemented high fat low carbohydrate diet.…”
Section: The Ketogenic Diet: Overview and Preclinical Evidencementioning
confidence: 99%
“…Our study shows that as glucose levels are diminished, GBM cells can adapt by at least partially shifting their metabolism to accommodate ketone body oxidation. Prior animal studies investigating the therapeutic potential of the KD have yielded mixed results, usually depending on the manner of administration and ability to achieve ketosis 18,20,49,50 . One study using U87 cells in a mouse tumor model found that an ad libitum KD resulted in increased blood ketone levels without affecting blood glucose or tumor growth 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Another seven animal studies [72][73][74][75][76][77][78] and nine human studies [79][80][81][82][83][84][85][86][87] were identified by the secondary search process. Subsequently, 14 animal studies were excluded because they either initiated the KD prior to tumor cell injection [41,43,66,67], had no control group [44] or because they basically replicated the results of a previously published tumor model system ( [37,38,73] replicated [36], [74] replicated [42], [57] replicated [75], [59] replicated [51], [78] replicated [56], and [60,65] replicated [45,47]). A flow chart of the search process is given in Figure 1.…”
Section: Resultsmentioning
confidence: 99%